CCTV and Campus Crime: Challenging a Technological “Fix”: - Liedka, Raymond V. (Criminal justice policy review, 2019)
Universities using closed circuit television (CCTV) systems often tout its deterrent role when justifying the use of this technology. Using a sample of 336 U.S. universities, we examine the relationship between CCTV and reported crime rates using Clery Act crime data to discern whether CCTV has a deterrent impact on campus crime, controlling for other variables. We find that CCTV appears to have little to no impact. Rather, crime rates are associated with location (suburban, urban, rural), institutional control (public, private), student population density, level of tuition and fees, student-body demographics (e.g., gender, race), and crime control practices other than CCTV (e.g., scheduled security patrols, student transportation/escort services). These relationships differ by type of crime (e.g., property vs. violent). Implications for policy and future research are discussed.